2013
DOI: 10.1080/09064710.2013.782424
|View full text |Cite
|
Sign up to set email alerts
|

Growth characteristics, nutrient uptake, and metal accumulation of ryegrass (Lolium perenneL.) in sludge-amended mudflats

Abstract: The objective of this study was to investigate the impact of sewage sludge amendment (SSA), with the rates of 0, 30, 75, 150, and 300 t ha (1 , on soil chemical properties and biomass, aboveground and root growth, and nitrogen and phosphorus uptake of ryegrass (Lolium perenne L.) seedling grown on a mudflat soil. Results showed that SSA modified the chemical properties of mudflat soil by decreasing soil salinity and pH, increasing soil organic matter, total and available N and P, and heavy metals. The biomass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
(36 reference statements)
2
14
0
Order By: Relevance
“…The pH in mudflat salt-soil decreased with increasing SSA rates, which was similar to our previous studies [9,20,21]. Other authors have also found lowering of pH with SSA [50][51][52].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The pH in mudflat salt-soil decreased with increasing SSA rates, which was similar to our previous studies [9,20,21]. Other authors have also found lowering of pH with SSA [50][51][52].…”
Section: Discussionsupporting
confidence: 90%
“…Our previous studies also supported the results [9,20,21]. In farmland, soil fertility improvement by SSA has also been reported widely [50,51,54].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The newly reclaimed mudflats are high in salinity and not suitable for cultivation as indicated by poor soil structure, extremely low organic matter (OM) content, low nutrient level, and lack of microbial diversity. The keys to mudflat reclamation to arable-lands are to reduce salinity, and to increase the soil OM content thus soil fertility [4]. Salinity reduction is often accomplished through freshwater irrigation.…”
Section: Introductionmentioning
confidence: 99%